Challenges of Economic of Georgia: Good and Bad EconomicGrowth - Kasradze, Tea; Zarnadze, Nino (European Journal of Economics and Business Studies, 2022)
The Georgian economy has been undergoing serious transformations over the years. The reforms carried out by the government affected all spheres of the economy - health care, education, industry, the military-technical complex, etc. The annual growth of the economy is approximately 4.8%. The EU, partner developed countries and donor international organizations allocate huge financial resources for the implementation of the changes planned by the government. Despite this, the economy of Georgia is in a difficult situation. The reason of economic stagnation in which the country has been for years is an extensive vector of development of the national economy. Investment projects carried out in the country in recent years are extensive in most cases. These projects are aimed at increasing current profits. They mostly are not oriented to long-term perspective. Intensification projects based on scientific and technical progress that are capable to change the level of production qualitatively are few. Despite the lack of an innovative scientific and technical background the economic indicators are increasing. However, the analysis of the indicators’ growth factors shows the lack of development of the national economic system. The data does not reflect the real economic statement and point to an extensive (so-called bad growth) growth of the national economy and will lead to economic and political crisis. The intensive and extensive factors of economic growth is discussed and analyzed in the paper. The recommendations and measures are developed by the authors for improving the economy through the intensification of production processes.